546 Patient Opinions on Care Received in Virtual Clinics Compared to A Face-To-Face Clinic Appointments in General Surgery During The COVID-19 Pandemic. A Retrospective Patient Feedback Study. (4th May 2021) - Fanning, S; Palmer, H; Sturrock, B; Hussain, A; Carney, C; Jaunoo, S
Abstract: Introduction: Virtual clinics were implemented during COVID-19 to reduce patient contact. We identified the need to seek feedback from patients relating to their perceptions on care received at a virtual clinic compared to a face-to-face clinics. Method: Patients who attended a virtual clinic in General Surgery were selected at random from a database of 627 patients. They were called and asked to complete a google survey which was sent via email. A shorter survey was also conducted over the phone for patients who did not have an email address. Results: 79.6% (n = 43) of patients felt their care did not suffer because of non-face-to-face contact. 63% (n = 34) reported that their symptoms were fully assessed during the virtual clinic. 77.8% (n = 42) did not feel rushed by the virtual clinic, 92.6% (n = 50) answered that they had the opportunity to ask questions. 68.5% (n = 35) answered their care did not suffer by not being examined. 72.2% (n = 39) felt that the outcome of the clinic was not changed because of non face-to-face contact. Conclusions: Patient feedback on the care received in the virtual clinic was positive. This may suggest that virtual clinics could be utilised in outpatients care with good reception from patients.